Efficacy of Intra Sheath Corticosteroid Injection in Treatment of De Quervain Disease - Mahmood, Qasim; Mustafa, Sheraz; Nasir, Sarmad; Khalid, Noman (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the efficacy of intra-sheath corticosteroid injection in the treatment of De Quervain disease in patients presenting to Pakistan Atomic Energy Commission Hospital Islamabad. Methods: A total of 110 patients of both genders with De Quervain disease were included in the study. Injections were performed a maximum of three times, with an interval of 2 weeks between injections. Patients were called for follow-up 3 months after the last injection and efficacy was noted. Results: The age range in this study was from 30 to 70 years with a mean age of 49.354±6.37 years, a mean duration of complaints of 9.336±2.71 weeks and a mean baseline VAS score was 6.290±1.16. The right-hand side was more involved (81.8%) than the left-hand (18.2%). Efficacy was observed in 80% of patients. Conclusion: In summary, local steroid injections directly into the tendon sheath are a very efficient way to reduce the inflammation linked to De Quervain's illness; this method works far better than other therapies such as topical lotions, braces, and oral NSAIDs. This highlights the significant advantages that local steroid injections have over conventional pain management techniques, making them a desirable and effective therapeutic choice for individuals coping with the difficulties associated with De Quervain's disease.